Gamification in English for report writing: engaging learning through webinars - Syed Ahmad, Tuan Sarifah Aini; Zubir, Zurina; Kasawi, Alice Shanthi; Abd Rahman, Siti Fatimah; Abu Hassim, Aeimi Ruzanna (Universiti Teknologi MARA Cawangan Melaka, 2024)
Universiti Teknologi MARA (UiTM) has introduced an initiative known as Collaborative Group Collaborative Teaching (CGCT) that encourages lecturers to collaborate with academicians and expertise from local and international universities and industries. A CGCT project was conducted for English for Report Writing (EWC661) involving three lecturers from UiTM Seremban Campus and one lecturer from UiTM Shah Alam Campus. EWC661 was taught in 14 weeks with the aim to develop academic writing skills. Three webinars were conducted: (1) Paraphrasing and Citation, delivered by an invited speaker from International Islamic University Malaysia, (2) Preparing a Questionnaire for a Small Study, delivered by an invited speaker from Universiti Islam Sumatera Utara, Indonesia, and (3) The Report Template, delivered by a lecturer from the CGCT group. At the end of each webinar, students played a quiz game on Quizizz using the "Teacher-led" mode. Four gamification elements were applied in creating the quizzes namely leaderboard, score, verification feedback and time restriction. After the webinar sessions, students could access the webinar recordings and quizzes on Teams and the Quizizz website, respectively. A questionnaire was distributed to students at the end of the semester to evaluate their motivation in joining the webinars. Their motivation was feasured by using the ARCS Models consisting of four dimensions: attention, relevance, confidence and satisfaction. The results demonstrated that playing Quizizz at the end of the webinars grabbed students' attention, was relevant, increased their confidence in understanding the webinar contents and were satisfying in learning the contents. They were also motivated to join the webinars and play Quizizz at the end of the webinar. They believed that having Quizizz at the end of the webinars was fun and motivating. Therefore, the results suggest that gamification is essential to engage students in webinars for learning.